Ministry of Electricity and Renewable Energy Ministerial Decree No. 207 of the Year 2023 Issued on 17/8/2023 = وزارة الكهرباء والطاقة المتجددة قرار وزارى رقم 207 لسنة 2023 صادر بتاريخ 17/8/2023 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic